A descriptive study of associated factors with HIV/AIDS among antiretroviral users of Eastern Nepal - Khanal, VK; Rayamajhi, RB; Neupane, B; Kafle, SU; Thapa, B; Karki, P; Paudel, IS; Jha, N (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: In Nepal, the firstcase of Human Immunodeficiency Virus (HIV) was reported in 1988, since then the epidemic is driven by sexual transmission and intravenous drug use. The aim of this research is to study various associated factors with HIV/AIDS patients. MATERIALS AND METHODS: A cross-sectional study was carried out from May 2009 – April 2010 at three Anti-retroviral treatment centers (B.P.K.I.H.S, Dharan, Koshi Zonal Hospital, Biratnagar and Mechi Zonal Hospital, Bhadrapur). A purposive sampling technique was applied to include all 234 seropositive patients who were under medication from these centers. RESULTS: Males represented 71% of the patients. More than 75%of the patients fell in the age group of 20-39 years. 35.9% of them had visited commercial sexual workers and similar proportion of them had shared needles during intravenous drug use. CONCLUSIONS: Unsafe high risk behavior with commercial sexual worker and needle sharing habit were found to be the associated with HIV/AIDS patients. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8667 Int J Infect Microbiol 2013;2(3):95-98